2019
DOI: 10.1002/rth2.12213
|View full text |Cite
|
Sign up to set email alerts
|

Protease‐activated receptor‐mediated platelet aggregation in acute coronary syndrome patients on potent P2Y12 inhibitors

Abstract: Background Despite the increasing use of potent P2Y12 inhibitors, further atherothrombotic events still impair the prognosis of many acute coronary syndrome (ACS) patients. This may in part be attributable to intact platelet aggregation via the human thrombin receptors protease‐activated receptor (PAR)‐1 and PAR‐4. Objective We studied PAR mediated platelet aggregation in ACS patients following percutaneous coronary intervention (PCI) with stent implantation in a cross‐sectional study. Methods Platelet aggrega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 53 publications
(73 reference statements)
0
34
0
Order By: Relevance
“…On-treatment residual AA-and ADP-inducible platelet reactivity was significantly higher in patients with ACE inhibitors as compared to patients with ARBs (AA: 17 AU [12][13][14][15][16][17][18][19][20][21][22] vs. 13 AU [7][8][9][10][11][12][13][14][15][16][17][18], p = 0.006; ADP: 20 AU (16-24) vs. 16 AU (11)(12)(13)(14)(15)(16)(17)(18)(19)(20), p < 0.001; Table 2, Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On-treatment residual AA-and ADP-inducible platelet reactivity was significantly higher in patients with ACE inhibitors as compared to patients with ARBs (AA: 17 AU [12][13][14][15][16][17][18][19][20][21][22] vs. 13 AU [7][8][9][10][11][12][13][14][15][16][17][18], p = 0.006; ADP: 20 AU (16-24) vs. 16 AU (11)(12)(13)(14)(15)(16)(17)(18)(19)(20), p < 0.001; Table 2, Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…However, atherothrombotic events still impair the prognosis of many patients with ACS despite state-of-the-art antiplatelet therapy [6]. While high on-treatment residual platelet reactivity (HRPR) to ADP is a rare phenomenon in patients treated with prasugrel or ticagrelor [7], subsequent ischemic events in patients receiving the novel P2Y12 antagonists may in part be attributable to platelet activation via other, non-inhibited pathways [8][9][10]. In addition, previous studies have identified several concomitant pharmacological therapies potentially attenuating the antiplatelet effects of clopidogrel [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…NPA are a sensitive marker of platelet activation and reflect the extent of neutrophil-platelet interaction [ 18 , 41 ]. TRAP is a strong protease activated receptor−1 agonist leading to pronounced platelet activation despite dual antiplatelet therapy [ 42 , 43 ]. Moreover, we have previously shown that TRAP inducible platelet surface expression of P-selectin and activated glycoprotein IIb/IIIa are associated with ischemic events after peripheral angioplasty and stenting [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in previous studies we have shown that alternative platelet activation pathways, i.e. toll- like (TLR) and protease- activated receptor (PAR) signaling, remain active despite P2Y 12 inhibition with prasugrel or ticagrelor, 33 , 49 pointing at the possibility that even these potent drugs are associated with HRPR.…”
Section: Discussionmentioning
confidence: 99%
“…Whole blood impedance aggregometry was performed with the Multiplate analyzer (Roche Diagnostics, Mannheim, Germany) as previously described. 29 , 33 One Multiplate test cell contains 2 independent sensor units and 1 unit consists of 2 silver-coated highly conductive copper wires with a length of 3.2 mm. After dilution (1:2 with 0.9% NaCl solution) of hirudin-anticoagulated whole blood and stirring in the test cuvettes for 3 minutes at 37°C, ADP (6.4 μM, Roche Diagnostics, Mannheim, Germany) or arachidonic acid (AA; final concentration of 0.5 mM; Roche Diagnostics, Mannheim, Germany), was added and aggregation was continuously recorded for 6 minutes.…”
Section: Methodsmentioning
confidence: 99%